Potential Roles of Exosomes in Parkinson’s Disease: From Pathogenesis, Diagnosis, and Treatment to Prognosis - Yu, Haiyang; Sun, Tong; An, Jing; Wen, Lulu; Liu, Fei; Bu, Zhongqi; Cui, Yueran; Feng, Juan (Frontiers in Cell and Developmental Biology, 2020)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease in the world, after Alzheimer’s disease (AD), affecting approximately 1% of people over 65 years of age. Exosomes were once considered to be cellular waste and functionless. However, our understanding about exosome function has increased, and exosomes have been found to carry specific proteins, lipids, functional messenger RNAs (mRNAs), high amounts of non-coding RNAs (including microRNAs, lincRNAs, and circRNAs) and other bioactive substances. Exosomes have been shown to be involved in many physiological processes in vivo, including intercellular communication, cell migration, angiogenesis, and anti-tumor immunity. Moreover, exosomes may be pivotal in the occurrence and progression of various diseases. Therefore, exosomes have several diverse potential applications due to their unique structure and function. For instance, exosomes may be used as biological markers for the diagnosis and prognosis of various diseases, or as a natural carrier of drugs for clinical treatment. Here, we review the potential roles of exosomes in the pathogenesis, diagnosis, treatment, and prognosis of PD.